Anthelmintic resistance of horse strongyle nematodes to ivermectin in São Paulo state, Brazil - de Favare, Giordani Mascoli [UNESP]; de Almeida Cipriano, Isabela [UNESP]; do Carmo, Tábata Alves [UNESP]; Mena, Mateus Oliveira [UNESP]; Guelpa, Gabriel Jabismar [UNESP]; do Amarante, Alessandro Francisco Talamini [UNESP]; de Soutello, Ricardo Velludo Gomes [UNESP] (Elsevier, 2023)
The indiscriminate use of drugs to control gastrointestinal helminths in horses can lead to serious consequences for the animals, which represents a growing problem for health, animal welfare and productivity. Therefore, the present study aimed to evaluate the anthelmintic efficacy of ivermectin in naturally infected horses in the western region of the state of São Paulo. From May 2021 to April 2022, 123 naturally infected adult horses in 12 equine breeding farms (7 to 14 animals per farm) were evaluated with the fecal egg count reduction test. The horses had not been treated with anthelmintic drugs for at least 60 days before the start of the study. The animals were treated with ivermectin (0.2 mg/kg; Eqvalan®, Merial) administered orally according to recommended dosage by the manufacturer. Individual fecal samples were collected directly from the rectal ampulla and used to determine the eggs per gram of feces (EPG) and perform coproculture for identification of larvae on the day of anthelmintic treatment (D0) and 14 days later (D14). The fecal egg count reduction (FECR) on each property was calculated using the program Shiny-egg Counts R version 3.6.1, and the presence of anthelmintic resistance was confirmed when the FECR percentage was less than 95%, and when the lower confidence limit [LCI] was less than 90%. The pre-treatment average EPG count in the 12 properties was 991. In five properties the FECR was lower than 90%; in three properties between 90% and 95%; and in four properties equal to or greater than 95% after treatment with ivermectin. The occurrence of cyathostomins with resistance to ivermectin was recorded in the majority of the farms.
Keywords: Cyathostomins; Equines; Helminths; Strongylus